The open-ocean missing backscattering is in the structural complexity of particles - Emanuele Organelli (Nature Portfolio, 2018)
Particulate optical backscattering is key to studying the oceanic carbon pump though it remains unclear what particles are detected. Here the authors show that complex particles larger than 1 µm help reproduce all the measured backscattering across the Atlantic Ocean and explain the majority of the signal.